ANNOUNCER’S SKILLS DAN PERANANNYA DALAM MENINGKATKAN KUALITAS SIARAN RADIO - Anita Trisiah (Wardah, 2013)
Information is an essential thing required by every human being both as a personal and as a social creature. There are many channels that human can use to get the information, and one of them is radio. One of keys by which radio could success is by having announcers which have good skills. The skills are communications of idea, communications of personality, projection of personality consisted of naturalness, vitality, and  friendliness, pronounciation, and voice control consisting of picth, loudness, time, and quality. Through and interview, observation and literature study, it is achieved that being an announcer is not that very simple. The announcers should master the skills to the most that they could perform very well as the dramaturgist theory suggests.